FACTS device installation in transmission system using whale optimization algorithm - Irham Syafiq Shahbudin; Ismail Musirin; Saiful Izwan Suliman; Afdallyna Fathiyah Harun; Sharifah Azma Syed Mustaffa; Hadi Suyono; Nor Azura Md Ghani (Institute of Advanced Engineering and Science, 2019)
As the world is progressing forward, the load demand in the power system has been continuously increasing day by day. This situation has forced the power system to operate under stress condition due to its limitation. Therefore, due to the stressed condition, the transmission losses faced higher increment with a lower minimum voltage. Theoretically, the installation of the Flexible AC Transmission System (FACTS) device can solve the problem experienced by the power system. This paper presents the whale optimization algorithm for loss minimization using FACTS devices in the transmission system. Thyristor controlled series compensator (TCSC) is chosen for this study. In this study, WOA is developed to identify the optimal sizing of FACTS device for loss minimization in the power system. IEEE 30- bus RTS was used as the test system to validate the effectiveness of the proposed algorithm.